Predictors of short‐ and long‐term outcomes of patients undergoing transcatheter mitral valve edge‐to‐edge repair. Issue 3 (12th June 2020) - Geyer, Martin; Keller, Karsten; Born, Sonja; Bachmann, Kevin; Tamm, Alexander R.; Ruf, Tobias F.; Kreidel, Felix; Hahad, Omar; Ahoopai, Majid; Hobohm, Lukas; Beiras‐Fernandez, Andres; Kornberger, Angela; et al.
Abstract: Objectives: Transcatheter mitral valve repair (TMVR) by edge‐to‐edge therapy is an established treatment for severe mitral valve regurgitation (MR). Background: Symptomatic and prognostic benefit in functional MR has been shown recently; nevertheless, data on long‐term outcomes are sparse. Methods and results: We analyzed survival of patients treated with isolated edge‐to‐edge repair from June 2010 to March 2018 (primarily combined edge‐to‐edge repair with other mitral valve interventions was excluded) in a retrospective monocentric study. Overall, 627 consecutive patients (47.0% females, 78.6 years in mean) were included. Leading etiology was functional MR (57.4%). Follow‐up regarding survival was available in 97.0%. While 97.6% were discharged alive, 75.7% were alive after a 1‐year, 54.5% after 3‐year, 37.6% after 5‐year and 21.7% after 7‐year follow‐up. Higher logistic Euroscores and comorbidities such as COPD and renal insufficiency were associated with higher in‐hospital and 1‐year mortality. Importantly, in‐hospital survival increased over the years. Conclusions: With the present study we established high survival rates at discharge and after 1 year of patients treated with TMVR. This goes along with high implantation numbers, increased interventional experience and a better in‐hospital survival over the years. Long‐term mortality in turn was substantially influenced by comorbidities.